Cardiovascular Biomarkers for Prediction of in-hospital and 1-Year Post-discharge Mortality in Patients With COVID-19 Pneumonia - Motloch, Lukas J.; Jirak, Peter; Gareeva, Diana; Davtyan, Paruir; Gumerov, Ruslan; Lakman, Irina; Tataurov, Aleksandr; Zulkarneev, Rustem; Kabirov, Ildar; Cai, Benzhi; Valeev, Bairas; Pavlov, Valentin; et al. (Frontiers in Medicine, 2022)
Aims: While COVID-19 affects the cardiovascular system, the potential clinical impact of cardiovascular biomarkers on predicting outcomes in COVID-19 patients is still unknown. Therefore, to investigate this issue we analyzed the prognostic potential of cardiac biomarkers on in-hospital and long-term post-discharge mortality of patients with COVID-19 pneumonia. Methods: Serum soluble ST2, VCAM-1, and hs-TnI were evaluated upon admission in 280 consecutive patients hospitalized with COVID-19-associated pneumonia in a single, tertiary care center. Patient clinical and laboratory characteristics and the concentration of biomarkers were correlated with in-hospital [Hospital stay: 11 days (10; 14)] and post-discharge all-cause mortality at one year follow-up [FU: 354 days (342; 361)]. Results: 11 patients died while hospitalized for COVID-19 (3.9%), and 11 patients died during the one-year post-discharge follow-up period (n=11, 4.1%). Using multivariate analysis, VCAM-1 was shown to predict mortality during the hospital period (HR 1.081, CI 95% 1.035;1.129, p=0.017), but not ST2 or hs-TnI. In contrast, during one-year FU post hospital discharge, ST2 (HR 1.006, 95% CI 1.002;1.009, p<0.001) and hs-TnI (HR 1.362, 95% CI 1.050;1.766, p=0.024) predicted mortality, although not VCAM-1. Conclusion: In patients hospitalized with Covid-19 pneumonia, elevated levels of VCAM-1 at admission were associated with in-hospital mortality, while ST2 and hs-TnI might predict post-discharge mortality in long term follow-up.